2012
DOI: 10.1177/0040517511435010
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of military body armor due to wear: Laboratory testing

Abstract: Personal armor, including body armor, is protective clothing designed to either absorb or deflect attacks that would usually be fatal to an individual. These attacks include, but are not limited to, slashing, bludgeoning, stabbing and ballistic threats. In the UK, body armor is worn by police officers for their shift; however, military personnel (particularly when based overseas) may wear body armor continuously for much longer time periods. Thus, the effect of wear due to use on the performance of body armor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…3 * 16 (5) where are: l -the length of the sample, b -the width of the sample, h -the thickness of the sample, F -the force, and A -the deflection [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 * 16 (5) where are: l -the length of the sample, b -the width of the sample, h -the thickness of the sample, F -the force, and A -the deflection [14].…”
Section: Resultsmentioning
confidence: 99%
“…The 'soft body armor' is usually constructed of the multiple layers of the fabric commonly known as the 'ballistic panel', which is injected into a 'carrier' composed of a polyester/cotton or nylon woven fabric and may be inserted into a light-resistant (or water-resistant) cover. The 'soft body armor' worn by police officers is produced to provide protection from stab threats and hand-gun bullets, while the military body armor is designed to bring protection from fragmentation threats, which are the most frequent injuries in modern war fighting [5]. There has been a significant development of new highperformance armor materials for lightweight http://www.jeffjournal.org Volume 9, Issue 4 -2014 body-armor and lightweight vehicle-armor structures.…”
Section: Introductionmentioning
confidence: 99%
“…All ballistic protective materials are susceptible to degradation over time and under certain conditions, 31 although fixed lifetimes for current military body armour systems do not exist. DuPont published the only recommendations in the mid-1980s, 32 stating that para-aramid fibre-based body armour should be replaced every 5 years and this has become the basis of the body armour vest replacement policy for many nations.…”
Section: Degradation and Wearmentioning
confidence: 99%
“…Although compromised plates have shown that they may be able to resist a threat 2 , the level of protection is very difficult to determine therefore any damage to armour results in its withdrawal from service 3 . Generally, aging is perceived not to be a significant contributing factor to the degradation of hard armour but may effect soft armour 4 .…”
Section: Introductionmentioning
confidence: 99%